Sistem Kontrol Kecepatan Motor Berdasarkan Enam Arah Pergerakan Kepala Menggunakan Facial Landmark Mata - Gagana Ghifary Ilham; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Persons with disabilities are normal people with limitations in doing something. One type of disability is a person with a physical disability, while a person with a disability does everything that needs help from others. Wheelchairs, for example wheelchairs. In this wheelchair can facilitate mobility of people with disabilities, but at the time when the compilation of disabled people appears not only defects in the legs due to defects in the hands as well, so to use this wheelchair will also feel difficult and still need help from others. This problem can actually be above by using a remote or joystick in order to control the wheelchair. The research was carried out in order to help people with physical disabilities intended for people with multiple physical disabilities and was designed to utilize head movements using digital image processing using cameras and facial landmark methods. In processing data on the system using Arduino nano and implementing output using dual L293d motor. The test was carried out using 6 people using different times and distances from the face objects on each head movement. The average test result for movement based on distance and time for all test subjects is 100%. Whereas in the movement of looking up at night the distance of 50 cm and 30 cm, and during the day at a distance of 30 cm also get an average gain of 98.75% in one of the test subjects. The effect of time and distance is very important in conducting this research.